EVALUASI PENGARUH LAJU ALIR POMPA INJEKSI TERHADAP TEKANAN POMPA INJEKSI PADA STASIUN PENGUMPUL UTAMA B JATIBARANG FIELD - Fifi Izzati; Riska Laksmita Sari Riska Laksmita Sari; Adhy Rahutomo Saptandro (Jurnal Natural, 2022)
After a certain period of time, the reservoir's pressure will drop to the point where petroleum can no longer flow naturally. Because of the decrease in oil production, a well will no longer have economic value. Artificial lifts or specific methods are used in wells to help oil flow to the surface in order to maintain or increase petroleum recovery. Water injection is a method of increasing oil recovery by injecting water into the well. Water injected into this well will increase pressure to the oil in the reservoir, causing it to be pushed and flow to the surface. Water treatment is typically performed at a Water Treatment Injection Plant (WTIP). WTIP performance is an activity that is used to keep reservoir pressure constant. The separation of the water that is lifted with the oil is the first step in the WTIP process. The Jatibarang Field fluid is collected at the SPU (Main Collector Station). Water from various wells will be collected at the SPU A, SPU B, SPU-Cemara, and Balongan terminals. At WTIP SPU B, the injection pump flow rate and injection pressure have a linear or directly proportional relationship. This is because as the injection pump flow rate increases, the amount of water injected increases, causing the pressure to increase. The flow rate is influenced by the amount of water received at SPU B, the condition of the pump, and the line connecting the SPU and WTIP.